Communication Pattern of Symbolic Interactionism Between Deaf Disabled Workers and Deaf Non-Disabled Workers at Ketje Jambi Coffee Cafe - Febiola Francisca; Damri Damri (Universitas Muhammadiyah Enrekang, 2023)
This research was motivated by the discovery of deaf disability workers at the Ketje Jambi Coffee Cafe. The findings attracted researchers' curiosity about how communication patterns between workers. Based on these findings, a research problem formulation was obtained, namely